Menakar Keraguan Penggunaan QR Code Dalam Transaksi Bisnis - Ni Luh Novi Arianti; Gede Sri Darma; Luh Putu Mahyuni (Universitas Pendidikan Nasional, 2019)
ABSTRACT Currently payment using the QR code is one of the most important in mobile payment. Based on data from the Bali Provincial Statistics Agency in 2017, the highest number of cellular phone users was Denpasar Regency, which was equal to 80.88% while the lowest user was Bangli Regency, which was 53.26%. The purpose of this study is to analyze customer acceptance in the use of mobile payment specifically the QR Code and find out the strategies used in order to expand the reach of QR Code. The writing method is qualitative with interviews and documentation with the merchant QR Code and customers who make mobile payment transactions. The results of the study include acceptance of qr code in business transactions, soit can be concluded that the QR Code has not been accepted in business transactions and the provision of information still needs to be improved by implementing better strategies and socialization from the bank so that the program being launched runs as expected. The results of this study are expected to contribute to the banks regarding the programs that have been implemented, especially payment methods with qr code, can be used as a reference by leaders and marketing in banking companies in decision making and also as a guide for developing banking payment methods and making payment methods a solution future payment.